The comparative short-term efficacy and safety of drug-coated balloon vs. drug-eluting stent for treating small-vessel coronary artery lesions in diabetic patients - Li, Kui; Cui, Kaijun; Dan, Xuechuan; Feng, Jian; Pu, Xiaobo (Frontiers in Public Health, 2022)
Purpose: This meta-analysis aimed to explore the comparative efficacy and safety of drug-coated balloon (DCB) versus drug-eluting stent (DES) for treating small-vessel coronary artery lesions in diabetic patients. Methods: We searched PubMed, EMBASE, the Cochrane Library, and China National Knowledgement Infrastructure (CNKI) for retrieving relevant studies regarding the comparison of DCB with DES in treating small-vessel coronary artery lesions in diabetic patients until 31 May 2022. Two independent authors screened study, extracted data, and assessed methodological quality. Then, the meta-analysis was conducted using RevMan software, version 5.4. Results: We included 6 studies with 847 patients in this meta-analysis. Pooled results showed that DCB was associated with fewer major adverse cardiac events (MACE) (RR, 0.60; 95% confidence interval [CI], 0.39 to0.93; p=0.02), myocardial infarction [MI] (RR, 0.42; 95% CI, 0.19 to 0.94; p=0.03), target lesion revascularization [TLR] (RR, 0.24; 95% CI, 0.08 to 0.69; p<0.001), target vessel revascularization [TVR] (RR, 0.33; 95% CI, 0.18 to 0.63; p<0.001), binary restenosis (RR, 0.27; 95% CI, 0.11 to 0.68; p=0.005), and late lumen loss (LLL) (mean difference [MD], -0.31; 95% CI, -0.36 to -0.27; p<0.001), but was comparable technique success rate, death, minimal lumen diameter (MLD), and net lumen gain (NLG) to DES. There was no difference in long-term outcomes between these two techniques. Conclusions: This meta-analysis shows that DCB is better than DES in treating small-vessel coronary artery lesions in diabetic patients. However, more studies are required to validate our findings and investigate the long-term effects and safety of DCB.